On the angle between two subspaces of an inner product space - Hendra Gunawan (KOMUNITAS Analisis Matematika INDONESIA, 2025)
In this paper, we shall discuss two formulae for the angle between two subspaces, or more generally the angle from a subspace of dimension p to another subspace of dimension q with 1pq(X), in an inner product space X. In particular, we shall see that the two seemingly different formulae, one is obtained by H. Gunawan, O. Neswan, and W. Setya-Budhi in 2005 and the other by N. Wildberger in 2017, are actually identical.